THE EFFECT OF POSITION PROMOTION AND COMPETENCY ON EMPLOYEE PERFORMANCE OF PT. LAMPUNG REGIONAL DEVELOPMENT BANK - Ahmaludin .; Junaidi . (Saburai International Journal of Social Sciences and Development, 2021)
The purpose of this study was to determine the effect of promotion and competence on PT employees' performance. Lampung Regional Development Bank. The hypothesis of this research is that promotion and competence affect the performance of employees in PT. Lampung Regional Development Bank.This research uses 56 employees as a sample. The research data techniques use the questionnaire method, documentation and observation. The data analysis method uses a quantitative approach with SPSS version 21.0 statistical tools, including the A validation test calculation, reliability test, linear regression test, T test, F test and coefficient of determination test.The hypothesis is the effect of job promotion on performance partially shows that job promotion has an effect on employee performance with a 61.8 % contribution. Competence affects employee performance with a 58 % contribution. Promotion and competence together have a positive and significant impact on employee performance with a 61.8 % contribution. The remaining 38.2% are other variables not examined, such as leadership style, discipline and so on.